Efektivitas Pelayanan Outreach Door To Door terhadap Pemberian Bantuan Program Padat Karya di Kelurahan Bangkingan Kota Surabaya - Julia Putri Anggraini; Rosyidatuzzahro Anisyukurillah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research uses a qualitative approach to see the effectiveness of door to door outreach services in the Labor Intensive Program in Bangkingan Village, Surabaya City. Secondary data sources for this research were obtained through interviews and observations of the implementation team and the community receiving assistance. Data analysis uses effectiveness theory according to Gibson et al (2003) with five indicators: production, effectiveness, satisfaction, adaptation and development. From the research results, it was found that the production process involved identification, data collection and re-examination of potential aid recipients. Program implementation involves a door to door outreach team which plays an important role in outreach, project implementation and monitoring. Distribution of aid was carried out in Bangkingan Village, along with a comprehensive evaluation after the program was implemented. The effectiveness of the program is measured through five indicators, and the analysis results show a positive impact on production, efficiency, satisfaction, adaptation and development. Door to door outreach services increase operational efficiency by providing better information accessibility, accurate data collection, and active community participation. The implementation team can overcome challenges and negative responses from the community through adaptation. Although some residents feel uncomfortable, providing education and ongoing evaluation helps minimize this discomfort. Community satisfaction is an important focus, direct interaction creates closer relationships. Challenges such as negative responses or citizen discomfort are overcome by increasing adaptation and communication. The involvement of sub-districts in door-to-door outreach services opens up opportunities to understand more deeply the conditions of the community, increase the efficiency and relevance of programs, and build closer relationships between the government and the community.